Association of custom-made zirconia abutments with emax crowns in implant rehabilitations: case report - Fernandes Jr, Virgílio Vilas Boas; Romero, Rogério de Lima; Feitosa, Pedro; da Silva, João Mauricio Ferraz; Aprobato, Gilberto (Brazilian Dental Science, 2014)
Today, the constant search for aesthetics by most patients together with the difficult in obtaining a natural appearance at the anterior area, especially in Implantology, helps to develop new methodologies to solve these problems. The aim of this study was to demonstrate through case report the applicability of custom-made zirconia abutments in association with IPS eMax metal-free crowns. The prostheses at the anterior area of maxilla were made on four teeth and three implants. Implant abutments were customized in zirconia through CAD/CAM system. Metal-free crowns were obtained through IPS eMax system for all elements. The patient was clinically and radiographically followed-up at seven, 15, 30 and 60 post-operative days, when it was observed the aesthetic-functional stability of the case. The final results met the expectations of the patient.